Intercultural Awareness in Indonesian EFL Classes - Madani, Akbar Ibrahim ((JELE) Journal Of English Language and Education, 2020)
Language and culture are inseparable. Foreign language learning is not only the language learning, but also the culture learning. Intercultural awareness, according to Chen and Starosta (1996), refers to an understanding of one’s own and others’ cultures that affect how people think and behave. The cultivation of students’ cultural awareness in EFL teaching can encourage students to break the obstacles of intercommunication and master the culture of the target language by analyzing a survey which investigates the students’ present condition of intercultural awareness. The key point of learning cultural knowledge and cultivating cultural awareness is to create a good learning environment in the classroom. Teachers should change the conventional concepts, as well as the attitudes of regarding exams as the standard of evaluating students’ ability. This paper tries to put forward some measures to cultivate the students’ intercultural awareness in EFL teaching.